Bibliometric and visual analysis of fecal microbiota transplantation research from 2012 to 2021 - Zhang, Fengwei; Yang, Peilin; Chen, Yilin; Wang, Ruirui; Liu, Baocheng; Wang, Jianying; Yuan, Min; Zhang, Lei (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Fecal transplantation (FMT) is an emerging therapy for diseases associated with intestinal flora imbalance that has attracted increasing attention in recent years. This study aims to provide an overview of research trends in the field, and act as a reference point for future scientific research by analyzing the state of current research, identifying hotspots, and potential frontiers of FMT. Methods: Articles relating to FMT that were published between the years 2012 and 2021 were retrieved from the Web of Science Core Collection. Bibliometric analysis was performed using Microsoft Excel and CiteSpace. Results: A total of 2,403 English language articles relating to FMT research were published over the last ten years. Most of this research was carried out in the United States of America, with Harvard Medical school being the most productive institution. Much of the research was published in the PLoS One journal. Alexander Khoruts was identified as a prominent, productive researcher in the field. Keyword analysis revealed that research hot spots included gut microbiota, Clostridium difficile infection (CDI), and diseases. Burst detection indicated that future research frontiers include clinical practice guidelines and strategies. Conclusion: Our analysis explored hot spots and emerging trends in the FMT field. Indications for use of FMT extended from digestive system diseases to other systemic diseases. Additionally, areas such as risk assessment and control, along with application methods were also a focus of current research. Moreover, research relating to optimization of clinical practice has excellent prospects.